Using Rutile TiO2 Nanoparticles Reinforcing High Density Polyethylene Resin. (27th May 2014) - Tuan, Vu Manh; Jeong, Da Woon; Yoon, Ho Joon; Kang, SangYong; Vu Giang, Nguyen; Hoang, Thai; Thinh, Tran Ich; Kim, Myung Yul
Abstract : The TiO2 nanoparticles were used as a reinforcement to prepare nanocomposites with high density polyethylene (HDPE) by melt blending process. The original TiO2 (ORT) was modified by 3-glycidoxypropyltrimethoxysilane (GPMS) to improve the dispersion into HDPE matrix. The FT-IR spectroscopy and FESEM micrographs of modified TiO2 (GRT) demonstrated that GPMS successfully grafted with TiO2 nanoparticles. The tensile test of HDPE/ORT and HDPE/GRT nanocomposites with various contents of dispersive particles indicated that the tensile strength and Young's modulus of HDPE/GRT nanocomposites are superior to the values of original HDPE and HDPE/ORT nanocomposites. At 1 wt.% of GRT, the mechanical properties of nanocomposites were optimal. In DSC and TGA analyses, with the presence of GRT in the nanocomposites, the thermal stability significantly increased in comparison with pure HDPE and HDPE/ORT nanocomposites. The better dispersion of GRT in polymer matrix as shown in FESEM images demonstrated the higher mechanical properties of HDPE/GRT nanocomposites to HDPE/ORT nanocomposites.